2018
DOI: 10.3389/fmicb.2018.02028
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Zika Virus Infection in Immunocompetent Mice Causes Postnatal Growth Impediment and Neurobehavioral Deficits

Abstract: A small percentage of babies born to Zika virus (ZIKV)-infected mothers manifest severe defects at birth, including microcephaly. Among those who appeared healthy at birth, there are increasing reports of postnatal growth or developmental defects. However, the impact of congenital ZIKV infection in postnatal development is poorly understood. Here, we report that a mild congenital ZIKV-infection in pups born to immunocompetent pregnant mice did not display apparent defects at birth, but manifested postnatal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 56 publications
7
25
1
Order By: Relevance
“…In our cohort, the most affected component was language. These results agree with several studies that used animal models and suggested ZIKV infection could cause postnatal developmental deficit [25,26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cohort, the most affected component was language. These results agree with several studies that used animal models and suggested ZIKV infection could cause postnatal developmental deficit [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…This is one of the hypothesis to explain cerebral injury [32]. Additionally lesions indicative of deep gray matter injury, vascular compromise and neuroprogenitor cell dysfunction are describe [25,26,33].…”
Section: Discussionmentioning
confidence: 99%
“…In our assays, we found body weight reduction in infected malnourished litters, consistent with the findings in human CZS cases. A recent study on wild-type C57BL/6J mice have found that vertical transmission of ZIKV after intraperitoneal injection on pregnant females does not result in morphological alterations in the offspring during perinatal life but negative outcomes appeared later in postnatal life (31). This coincides with our results of Co/ZIKV in which we confirmed ZIKV congenital infection, but we did not find phenotypic signals of CZS in embryos and neonates.…”
Section: Discussionsupporting
confidence: 91%
“…In a pigtail macaque model, maternal ZIKV inoculation during gestation resulted in substantial brain lesions and silent brain pathology (i.e., periventricular T2-hyperintense foci and loss of fetal noncortical brain volume, injury to the ependymal epithelium with underlying gliosis, and loss of late fetal neuronal progenitor cells) in fetuses, even in the absence of microcephaly [10,11]. Two very recent studies in immunocompetent mouse models reported neurocognitive disorders and neurobehavioral deficits in offspring affected with mild congenital ZIKV infection [12,13]. These pioneering studies provided critical information regarding outcomes of mild congenital ZIKV infection in mouse offspring.…”
Section: Introductionmentioning
confidence: 99%